Coated copper composite powder and its preparation method and application
By using coated copper composite powder, combining efficient mixing of copper powder and copper oxide powder and sintering technology with a lower sintering temperature, the existing copper powder preparation process is solved, and low energy consumption and performance are achieved Excellent copper heat pipe production.
Patent Information
- Application Number
- CN202211649100.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-21
AI Technical Summary
The existing copper powder preparation process is cumbersome, and it is difficult to meet the needs of copper heat pipes with low energy consumption and excellent performance in batch production.
The coated copper composite powder is used to efficiently mix the copper powder with copper oxide powder to form a composite copper powder with strong binding force, and sintered at a lower sintering temperature.
It has achieved a reduction in the sintering temperature by 200-300℃, reduced energy consumption, and improved the capillary force and permeability of the heat pipe.
Smart Images

Figure CN115889766B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal powder materials, and in particular relates to a coated copper composite powder and a preparation method and application thereof. Background Art
[0002] Porous metal materials have both structural and functional properties due to their special structure. They not only have a large specific surface area, excellent mass transfer performance, strong material adsorption capacity, permeability and shock absorption due to the pore structure, but also have high conductivity, excellent ductility and catalytic activity due to metal properties. They are a new type of functional porous structural material that is developing extremely rapidly and are often used to prepare various metal products such as heat dissipation materials, catalysts, electrode materials, filter plates, and oil-containing bearings. In recent years, with the rapid development of the radiator manufacturing industry, the performance requirements for metal heat pipe products have been continuously improved, and the structure and performance requirements of the porous copper powder raw materials used to prepare metal heat pipe products have also become increasingly higher.
[0003] For example, copper heat pipes are a type of efficient phase-change heat transfer element, and are widely used in the technical fields of heat transfer and heat dissipation. Currently, atomized copper powder is mainly used in copper heat pipe materials. The existing technology fills atomized copper powder with copper tubes for vibration compaction and sintering. This composite structure combining copper powder and copper tubes requires that the copper powder used must be more irregular on the one hand to ensure that after sintering, the pores in the capillary structure are more refined and exhibit stronger capillary force. On the other hand, it is also necessary to control the shrinkage rate of the copper powder to ensure that the copper powder and the inner wall of the copper tube have good bonding strength. In order to ensure the sintering strength, the sintering temperature usually needs to be set at around 930-970°C. On the one hand, this high-temperature sintering causes high energy consumption, and on the other hand, it also weakens the capillary structure and ultimately leads to a decrease in the capillary force of the copper tube structure.
[0004] Therefore, how to provide a copper powder whose preparation process is simple and suitable for mass production of copper heat pipes with low energy consumption and excellent performance is a technical problem that needs to be solved at present. Summary of the invention
[0005] The technical purpose of the present invention is to at least solve the problems that the existing copper powder preparation process is complicated and its performance cannot meet the requirements of mass production of copper heat pipes with low energy consumption and excellent performance.
[0006] This purpose is achieved through the following technical solutions:
[0007] In a first aspect, the present invention discloses a coated copper composite powder.
[0008] The copper composite powder is composed of copper powder and copper oxide powder, wherein the particle size of the copper powder is larger than the particle size of the copper oxide powder, and the copper oxide powder covers the outer periphery of the copper powder to form a coated copper composite powder, and the bulk ratio of the copper composite powder is 0.8 to 2.8 g / cm 3 The copper composite powder has large copper powder particles on the outside and small copper oxide particles on the inside. The small copper oxide particles are not easy to agglomerate, are brittle, and have high hardness. The small copper oxide particles are efficiently mixed with the soft large copper powder particles and partially undergo a mechanochemical reaction, forming a composite copper powder with strong bonding force.
[0009] In some embodiments of the present invention, the particle size distribution of the copper powder is between -50 and +400 mesh, and the D50 of the copper oxide powder is 0.5 to 5 μm.
[0010] In some embodiments of the present invention, the D50 of the copper oxide powder is 1.0 to 5 μm.
[0011] In some embodiments of the present invention, the particle size distribution of the copper powder includes: +60 mesh ≤ 2%, 50% ≤ -60 to +325 mesh ≤ 70 to 90%, -400 mesh ≤ 5%;
[0012] The microscopic morphology of the copper oxide powder is spherical or quasi-spherical.
[0013] In some embodiments of the present invention, the bulk ratio of the copper powder is between 2.4 and 4.0 g / cm 3 , preferably 2.5 to 3.0 g / cm 3 , which is at least one of electrolytic copper powder and atomized copper powder, and the purity of the copper powder is ≥97%.
[0014] In some embodiments of the present invention, the bulk ratio of the copper oxide powder is 0.7 to 1.5 g / cm 3 , preferably 0.7 to 1.0 g / cm 3 , which is cupric oxide and / or cuprous oxide.
[0015] In some embodiments of the present invention, the mass of the copper oxide powder is 2-15% of the mass of the copper powder.
[0016] In a second aspect, the present invention discloses a method for preparing the copper composite powder according to the first aspect, the method comprising efficiently mixing copper powder with copper oxide powder, wherein a mechanochemical reaction can partially occur during the efficient mixing process;
[0017] The efficient mixing includes low-speed fusion and high-speed fusion, wherein the speed of the low-speed fusion is 50-400 r / min and the time is 1-120 min;
[0018] The high-speed fusion has a rotation speed of 600 to 1000 r / min and a time of 1 to 120 min.
[0019] In a third aspect, the present invention discloses a heat sink, wherein the raw material of the heat sink is the copper composite powder described in the first aspect or the copper composite powder obtained by the method described in the second aspect.
[0020] In some embodiments of the present invention, the copper composite powder is formed and sintered using a heat sink mold, and the sintering temperature is 700-1000° C., preferably 700-800° C. The sintering temperature of the atomized copper powder used to prepare the heat pipe in the prior art is generally around 1000° C. By lowering the sintering temperature, the technical effect of reducing energy consumption can be achieved. In addition, the influence on the capillary force of the copper tube structure can also be reduced.
[0021] The beneficial effects of the technical solution disclosed in the present invention are mainly reflected in the following:
[0022] 1. The present invention provides a composite copper powder, which has a coated structure, wherein the coated copper composite powder has large-particle copper powder inside and small-particle copper oxide outside. The small-particle copper oxide is not easy to agglomerate, has strong brittleness and high hardness, and is efficiently mixed with soft large-particle copper powder and partially undergoes a mechanochemical reaction to form a copper composite powder with strong bonding force. The copper composite powder is used for heat pipe sintering. Since the copper oxide itself has a high specific surface area, it will promote sintering activity. During the sintering process, the copper oxide gradually loses oxygen, which will increase the porosity of the material and further increase the bonding force with the inner wall of the copper pipe. In addition, the sintering temperature can be reduced by 200-300°C, which is beneficial to reducing energy consumption.
[0023] 2. The present invention can adjust the bulk density of the compound copper powder by controlling the amount of copper powder and copper oxide powder, and ultimately achieve the beneficial effect of improving the capillary force and penetration force of the heat pipe.
[0024] 3. The present invention provides a compounding method for copper composite powder, which efficiently mixes copper powder and copper oxide powder with a certain bulk ratio and particle size to obtain a coated copper composite powder. The process is relatively simple and suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference numerals are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:
[0026] Figure 1 The microscopic morphology of the copper composite powder in Example 2 according to the embodiment of the present invention is schematically shown;
[0027] Figure 2 The microscopic morphology of the copper composite powder in Example 3 according to the embodiment of the present invention is schematically shown;
[0028] Figure 3 The coated microstructure of the copper composite powder according to the embodiment of the present invention is schematically shown. DETAILED DESCRIPTION
[0029] In the prior art, atomized copper powder is filled with copper tubes and vibrated and sintered. This composite structure of copper powder and copper tube requires that the copper powder used must be more irregular on the one hand to ensure that after sintering, the pores of the capillary structure are more refined and show stronger capillary force. On the other hand, it is also necessary to control the shrinkage rate of the copper powder to ensure that the copper powder and the inner wall of the copper tube have good bonding strength. In order to ensure the sintering strength, the sintering temperature usually needs to be set at about 930-970°C. On the one hand, this high-temperature sintering causes high energy consumption, and on the other hand, it will also weaken the capillary structure and ultimately lead to a decrease in the capillary force of the copper tube structure. Therefore, how to provide a copper powder that has a simple preparation process and can be used for mass production, low energy consumption, and excellent performance copper heat pipes is a technical problem that needs to be solved at present.
[0030] In order to solve the above technical problems, the present invention provides a coated copper composite powder and a preparation method and application thereof. The coated copper composite powder has large-particle copper powder on the outside and small-particle copper oxide powder on the inside. The small-particle copper oxide is not easy to agglomerate, has strong brittleness and high hardness, and is efficiently mixed with the soft large-particle copper powder and partially undergoes a mechanochemical reaction to form a composite copper powder with strong bonding force. The copper powder is used for heat pipe sintering. Since the copper oxide itself has a high specific surface area, it will promote sintering activity. During the sintering process, the copper oxide gradually loses oxygen, which will increase the porosity of the material and further increase the bonding force with the inner wall of the copper pipe. In addition, the sintering temperature can be reduced by 200 to 300°C. The present invention can adjust the bulk density of the composite copper powder by controlling the amount of copper powder and copper oxide, and finally improve the capillary force and permeability of the heat pipe.
[0031] At the same time, the "loose ratio" in the present invention is also called "loose density", and its measurement method is a commonly used method in the field.
[0032] The first aspect of the present invention to achieve the above technical effects is to provide a coated copper composite powder, the copper composite powder is composed of copper powder and copper oxide powder, wherein the particle size of the copper powder is larger than the particle size of the copper oxide powder, and the copper oxide powder covers the outer periphery of the copper powder to form a coated copper composite powder, and the bulk ratio of the copper composite powder is 0.8 to 2.8 g / cm 3 .
[0033] Exemplarily, the bulk ratio of the copper powder is 0.8 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.3g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 .
[0034] In some embodiments, the particle size distribution of the copper powder is between -50 and +400 mesh, and the D50 of the copper oxide powder is 0.5 to 5 μm, wherein 50 mesh corresponds to 270 μm, and 400 mesh corresponds to 38 μm.
[0035] In some embodiments, the particle size distribution of the copper powder includes: +60 mesh ≤ 2%, 50% ≤ -60 to +325 mesh ≤ 70 to 90%, -400 mesh ≤ 5%; wherein the "+" in front of the mesh number represents sifting, and the "-" represents unsifting.
[0036] The microscopic morphology of the copper oxide powder is spherical or quasi-spherical.
[0037] In some embodiments, the bulk ratio of the copper powder is 2.4 to 4.0 g / cm 3 , preferably 2.5 to 3.0 g / cm 3 , which is at least one of electrolytic copper powder and atomized copper powder, and the purity of the copper powder is ≥97%, where the purity refers to the mass percentage content of metallic copper, and the electrolytic copper powder and atomized copper powder are commercial products. In the present invention, the electrolytic copper powder is preferably electrolytic copper powder FTD, and the atomized copper powder is atomized copper powder FTW.
[0038] Exemplarily, the bulk ratio of the copper powder is 2.4 g / cm 3 , 2.5g / cm 3 , 2.6g / cm3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3 、3.1g / cm 3 、3.2g / cm 3 , 3.3g / cm 3 、3.4g / cm 3 , 3.5g / cm 3 、3.6g / cm 3 、3.7g / cm 3 、3.8g / cm 3 、3.9g / cm 3 , 4.0g / cm 3 .
[0039] In some embodiments, the bulk ratio of the copper oxide powder is 0.7 to 1.5 g / cm 3 , preferably 0.7 to 1.0 g / cm 3 , which is cupric oxide and / or cuprous oxide.
[0040] For example, the bulk ratio of the copper oxide powder is 0.7 g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 .
[0041] In some embodiments, the mass of the copper oxide powder is 2-15% of the mass of the copper powder.
[0042] Exemplarily, the mass of the copper oxide powder is 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or 15% of the mass of the copper powder.
[0043] The second aspect of the present invention to achieve the above technical effect is to provide a method for preparing the copper composite powder described in the first aspect, the method comprising efficiently mixing copper powder and copper oxide powder;
[0044] The efficient mixing includes low-speed fusion and high-speed fusion, wherein the speed of the low-speed fusion is 50-400 r / min and the time is 1-120 min;
[0045] The high-speed fusion has a rotation speed of 600 to 1000 r / min and a time of 1 to 120 min.
[0046] Exemplarily, the speed of the low-speed fusion is 50r / min, 80r / min, 100r / min, 120r / min, 150r / min, 180r / min, 200r / min, 220r / min, 250r / min, 280r / min, 300r / min, 320r / min, 350r / min, 380r / min, 400r / min. The time is 1min, 5min, 10min, 20min, 30min, 40min, 50min, 60min, 70min, 80min, 90min, 100min, 110min, 120min.
[0047] Exemplarily, the speed of the high-speed fusion is 600 r / min, 650 r / min, 700 r / min, 750 r / min, 800 r / min, 850 r / min, 900 r / min, 950 r / min, 1000 r / min, and the time is 1 min, 5 min, 10 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min.
[0048] The third aspect of the present invention to achieve the above technical effects is to provide an application of the copper composite powder described in the first aspect or the copper composite powder prepared by the method described in the second aspect in powder metallurgy, catalysts, heat dissipation materials, conductive coatings, and electromagnetic shielding materials.
[0049] The fourth aspect of the present invention to achieve the above technical effects is to provide a heat sink, the raw material of which is the copper composite powder described in the first aspect or the copper composite powder obtained by the method described in the second aspect.
[0050] In some embodiments, the copper composite powder is molded and sintered using a heat sink mold, and the sintering temperature is 700-1000°C, preferably 700-800°C.
[0051] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.
[0052] Example 1
[0053] Provides a bulk ratio of 2.8g / cm 3 The method for preparing copper composite powder comprises taking 90g of atomized copper powder and 10g of copper oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0054] The bulk ratio of the atomized copper powder is 3.8 g / cm 3 , particle size distribution includes: +60 mesh is 0.2%, -60 to +150 mesh is 85.0%, -400 mesh ≤1.2%;
[0055] The bulk ratio of the copper oxide powder is 1.5 g / cm 3 , D50=4.8μm.
[0056] Example 2
[0057] Provides a bulk ratio of 2.3g / cm 3 The method for preparing copper composite powder comprises taking 90g of atomized copper powder and 10g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0058] The bulk ratio of the atomized copper powder is 3.8 g / cm 3 , particle size distribution includes: +60 mesh is 0.2%, -60 to +150 mesh is 85.0%, -400 mesh ≤1.2%;
[0059] The bulk ratio of the cuprous oxide powder is 1.2 g / cm 3 , D50=2.8μm.
[0060] The microscopic morphology of the copper powder obtained in this embodiment is as follows: Figure 1 , combined with Figure 1 It can be seen that the target copper powder has been well wrapped.
[0061] Example 3
[0062] Provides a bulk ratio of 2.5g / cm 3 The method for preparing copper composite powder comprises taking 80g of atomized copper powder and 20g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0063] The bulk ratio of the atomized copper powder is 3.8 g / cm 3, particle size distribution includes: +60 mesh is 0.2%, -60 to +150 mesh is 85.0%, -400 mesh ≤1.2%;
[0064] The bulk ratio of the cuprous oxide powder is 1.5 g / cm 3 , D50 = 4.8 μm. The microscopic morphology of the copper powder obtained in this embodiment is as follows Figure 2 , combined with Figure 2 It can be seen that the target copper powder has been well wrapped, combined with Figure 3 It can be seen that an obvious encapsulating structure is formed.
[0065] Example 4
[0066] Provides a bulk ratio of 1.7g / cm 3 The method for preparing copper composite powder comprises taking 80g of atomized copper powder and 20g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0067] The bulk ratio of the atomized copper powder is 3.6 g / cm 3 , particle size distribution includes: +60 mesh is 0.2%, -60 to +150 mesh is 85.0%, -400 mesh ≤1.2%;
[0068] The bulk ratio of the cuprous oxide powder is 1.2 g / cm 3 , D50=2.8μm.
[0069] Example 5
[0070] Provides a bulk ratio of 2.0g / cm 3 The method for preparing copper composite powder comprises taking 90g of atomized copper powder and 10g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0071] The bulk ratio of the atomized copper powder is 2.3 g / cm 3 , particle size distribution includes: +60 mesh ≤ 2%, -60 ~ +150 mesh ≤ 55 ~ 70%, -400 mesh ≤ 5%;
[0072] The bulk ratio of the copper oxide powder is 1.7 g / cm 3 , D50=4.8μm.
[0073] Example 6
[0074] Provides a bulk ratio of 2.0g / cm 3The method for preparing copper composite powder comprises taking 98g of atomized copper powder and 2g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0075] The bulk ratio of the atomized copper powder is 2.5 g / cm 3 , particle size distribution includes: +60 mesh ≤ 2%, -60 ~ +150 mesh ≤ 55 ~ 70%, -400 mesh ≤ 5%;
[0076] The bulk ratio of the cuprous oxide powder is 1.2 g / cm 3 , D50=2.8μm.
[0077] Example 7
[0078] Provides a bulk ratio of 1.6g / cm 3 The method for preparing copper composite powder comprises taking 87g of atomized copper powder and 13g of cuprous oxide powder and mixing them in a three-dimensional mixer, first mixing at a low speed of 80r / min for 2min, and then mixing at a high speed of 600r / min for 3min.
[0079] The bulk ratio of the atomized copper powder is 2.5 g / cm 3 , particle size distribution includes: +60 mesh ≤ 2%, -60 ~ +150 mesh ≤ 55 ~ 70%, -400 mesh ≤ 5%;
[0080] The bulk ratio of the cuprous oxide powder is 1.2 g / cm 3 , D50=2.8μm.
[0081] Embodiments 8 to 9
[0082] A method for preparing copper composite powder is provided. The method increases the sintering temperature based on Example 7, and other aspects remain the same as Example 7.
[0083] The above embodiment uses atomized copper powder as copper powder, and electrolytic copper powder can also achieve the same technical effect as atomized copper powder.
[0084] The copper powders prepared in the above-mentioned Examples 1 to 9 are used to make heat pipes, and are tested according to the technical requirements of the heat pipe copper powder. The specific test method is: the sample is placed in a graphite mold and vibrated at a frequency of 50 Hz for 1 min, and then the graphite mold and the copper composite powder are placed in a sintering furnace at 750 to 950° C., wherein the sintering temperature of Examples 1 to 7 is 750° C., the sintering temperature of Example 8 is 850° C., and the sintering temperature of Example 9 is 950° C.; the sample is sintered at a constant temperature for 1.5 h in a hydrogen protective atmosphere, and then cooled to 40 to 60° C. with the furnace, and the graphite mold is taken out, and then the powder sintering sample is taken out.
[0085] Table 1 Properties of the copper composite powder for heat pipes prepared in each embodiment after sintering
[0086]
[0087] Among them, the standard used to calculate the porosity in Table 1 is GB / T 5163-2006, and the radial shrinkage test method is set and measured according to the industry standard YS / t 1337-2019 heat pipe copper powder mold. The maximum pore size test procedure is based on GB / T 5249-2013, and the permeability test procedure is based on GB / T 5250-2014. According to the test results, the porosity of the sample is significantly improved by increasing the coating amount, and better porosity and capillary force can be achieved at a lower sintering temperature (750°C).
[0088] In summary, the coated copper composite powder provided by the present invention can be sintered at a relatively low sintering temperature during sintering and can also achieve a better porosity and capillary force, so the copper composite powder provided by the present invention can effectively reduce energy consumption.
[0089] It should be understood that the terms used herein are only for the purpose of describing specific example embodiments and are not intended to be limiting. Unless the context clearly indicates otherwise, the singular forms "one", "an" and "said" as used herein may also be meant to include plural forms. The terms "include", "comprise", "contain", and "have" are inclusive and therefore indicate the presence of the stated features, steps, operations, elements and / or parts, but do not exclude the presence or addition of one or more other features, steps, operations, elements, parts, and / or combinations thereof. The method steps, processes, and operations described herein are not interpreted as requiring them to be performed in the specific order described or illustrated unless the execution order is clearly indicated. It should also be understood that additional or alternative steps may be used. The above description is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or replacements that can be easily thought of by a technician familiar with the technical field within the technical scope disclosed by the present invention should be included within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A coated copper composite powder, characterized in that: The copper composite powder is composed of copper powder and copper oxide powder, wherein the particle size of the copper powder is larger than the particle size of the copper oxide powder, the copper oxide powder covers the periphery of the copper powder to form a coated copper composite powder, and the bulk ratio of the copper composite powder is 2.0-2.8 g / cm 3 ; The copper powder is atomized copper powder.
2. The copper composite powder according to claim 1, characterized in that: The particle size distribution of the copper powder is between -50 and +400 meshes, and the particle size distribution of the copper oxide powder includes: D50 is 0.5 to 5 μm.
3. The copper composite powder according to claim 2, characterized in that: The particle size distribution of the copper oxide powder includes: D50 is 1.0 to 5.0 μm.
4. The copper composite powder according to claim 1, characterized in that: The particle size distribution of the copper powder includes: +60 mesh ≤ 2%, 50% ≤ -60 to +325 mesh ≤ 70 to 90%, and -400 mesh ≤ 5%.
5. The copper composite powder according to claim 1, characterized in that: The bulk ratio of the copper powder is 2.4 to 4.0 g / cm 3 ; and the purity of the copper powder is ≥97%.
6. The copper composite powder according to claim 5, characterized in that: The bulk ratio of the copper powder is 2.5-3.0 g / cm 3 .
7. The copper composite powder according to claim 1, characterized in that: The bulk ratio of the copper oxide powder is 0.7 to 1.5 g / cm 3 , the copper oxide is cupric oxide and / or cuprous oxide.
8. The copper composite powder according to claim 7, characterized in that: The bulk ratio of the copper oxide powder is 0.7 to 1.0 g / cm 3 .
9. The copper composite powder according to claim 1, characterized in that: The mass of the copper oxide powder is 2-15% of the mass of the copper powder.
10. A method for preparing the copper composite powder according to any one of claims 1 to 9, characterized in that: The method comprises efficiently mixing copper powder with copper oxide powder; The efficient mixing includes low-speed fusion and high-speed fusion, wherein the speed of the low-speed fusion is 50-400 r / min and the time is 1-120 min; The high-speed fusion has a rotation speed of 600 to 1000 r / min and a time of 1 to 120 min.
11. Use of the copper composite powder according to any one of claims 1 to 9 or the copper composite powder obtained by the method according to claim 10 in powder metallurgy, catalysts, heat dissipation materials, conductive coatings, and electromagnetic shielding materials.
12. A heat sink, characterized in that: The raw material of the heat sink is the copper composite powder according to any one of claims 1 to 9 or the copper composite powder obtained by the method according to claim 10.
13. The heat sink according to claim 12, characterized in that: The copper composite powder is molded and sintered using a heat sink mold, and the sintering temperature is 700-1000°C.
14. The heat sink according to claim 13, characterized in that: The sintering temperature is 700-800°C.
Citation Information
Patent Citations
Thermal conductive copper powder with high capillary rate and low apparent density and preparation method thereof
CN106238725A
Preparation method of low-apparent-density dry-method copper-coated iron powder, copper-coated iron powder and application of copper-coated iron powder
CN115026294A